Opportunistic Link Scheduling for Multihop Ad Hoc Wireless Networks - Shen, Min (My University, 2008)
This thesis studies throughput improvement for TCP traffic in IEEE 802.11-based multihop ad hoc wireless networks. Due to the Incompatibility between TCP and the IEEE 802.11 distributed coordination function (DCF) protocols, the reaction of TCP in case of packet losses can significantly reduce TCP end-to-end throughput. In this thesis, we propose an opportunistic link scheduling (OL8), which is a simple enhancement to the IEEE 802.11 DCF protocol and intends to improve the compatibility between TCP and MAC layer protocols in multihop ad hoc networks. With OL8, a link with a good channel condition is allowed to transmit multiple packets consecutively as a burst, while the burst size depends on both physical channel fading and MAC layer collisions. The protocol also includes a mechanism to prevent starvation of nodes with poor channel conditions. An analytical model is developed for a four-hop chain to study the effect of the burst size and TCP congestion window size on the end-to-end transmission throughput in opportunistic link scheduling. Our results show that OL8 can significantly improve the end-to-end transmission throughput, while keeping reasonably low transmission delay. The protocol is easy to implement, and requires slight modifications to the IEEE 802.11 protocol.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering